HPLC QUANTIFICATION OF LACTOPEROXIDASE IN THERAPEUTIC DAIRY WASTE ENRICHED BY BUBBLESEPARATION - Datta, Prabir K.; Mukhopadhayay, Goutam; Ghosh, Amitavo (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this study was to enrich therapeutic proteins and remove pollutants from dairy wastewater for establishing foam fractionation as a lucrative unit operation. Methods: Dairy wastewater collected from dairy industry was processed to fat-free dried protein waste mass diluted to 1-liter feed by distilled water in different concentrations and foam fractionated by sodium dodecyl sulphate (surfactant) to enriched proteins extract (foamate) in a foam fractionator. Foamate were analysed to quantify total proteins and lacto peroxidase respectively. The efficiency was evaluated by varying parameters like pH, initial waste and ionic concentrations, the waste-surfactant mass ratio of feed and flow rate of gas (N2) through feed solution by several experiments. Heat of desorption (λ) and mass transfer coefficient (K) were determined as indicators of adsorptive bubble separation to foam phase governed by Gibb’s equation of adsorption isotherm. Results: The process was optimized at pH 5.5, initial feed concentration 500μg/ml, waste–surfactant mass ratio (1.5:1), gas flow rate (350 ml/min) and ionic concentration 0.1 gram-mole of NaCL per litre of feed with enrichment factor (49.09), percent recovery (98.18%) observed in foamate. One natural preservative specifically lactoperoxidase was quantified by RP-HPLC analysis as 0.49% (w/w) of total proteins at optimal condition. Heat of desorption(λ), mass transfer coefficient(K)were determined 3140cal/mol and 12.68* 10-9 mol/cal/cm2/s respectively at pH 8.5, initial feed concentration 500μg/ml and gas flow rate 350 ml/min. Conclusion: The method may be a useful unit operation for recovery of biomolecules and removal of toxic pollutants from industrial wastewater for coming days.